2016
DOI: 10.1513/annalsats.201601-064oc
|View full text |Cite
|
Sign up to set email alerts
|

Global Associations between Air Pollutants and Chronic Obstructive Pulmonary Disease Hospitalizations: A Systematic Review

Abstract: Rationale: Exacerbations are key events in chronic obstructive pulmonary disease (COPD), affecting lung function decline and quality of life. The effect of exposure to different air pollutants on COPD exacerbations is not clear. Objectives:To carry out a systematic review, examining associations between air pollutants and hospital admissions for COPD exacerbations.Methods: MEDLINE, Embase, BIOSIS, Science Citation Index, and the Air Pollution Epidemiology Database were searched for publications published betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 67 publications
(87 reference statements)
2
40
0
Order By: Relevance
“…Meta-analysis is an important approach to synthesizing evidence across studies. So far, four analyses have been conducted to quantify the association between short-term ambient ozone exposure and COPD hospitalizations [13][14][15][16] (Table S1): one was focused solely on East Asia [13], one was based on publications before 2008 [14], and the other two, conducted in 2015 [15] and 2016 [16], simply reported pooled risk estimates. Since then, several original investigations have been published [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis is an important approach to synthesizing evidence across studies. So far, four analyses have been conducted to quantify the association between short-term ambient ozone exposure and COPD hospitalizations [13][14][15][16] (Table S1): one was focused solely on East Asia [13], one was based on publications before 2008 [14], and the other two, conducted in 2015 [15] and 2016 [16], simply reported pooled risk estimates. Since then, several original investigations have been published [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D insufficiency/deficiency and ambient air pollution are two major environmental factors that appear to influence the pathogenesis and stability of asthma [2] [3] [4] [5], as well as other respiratory diseases [6] [7]. However there remains debate resulting from the heterogeneity of findings relating to the effects of these environmental factors on airway pathology [5] [8] [9] [10]. For example, European studies have shown heterogeneity between different cities in the magnitude of the effects of pollution on health outcomes such as hospital admissions for respiratory diseases [9] and asthma incidence [11], despite using standardised analyses.…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of comparison, the results obtained by us point to a much higher RR, in the time perspective of 90 days obtaining the value 1.32. The authors of the meta-analysis underline that the relationship between the concentration of PM2.5 and COPD exacerbation becomes more distinct for higher concentrations of PM2.5 [19]. De Vries et al in their work empasise the significance of a delay in exerting the effect due to pollution and, consequently, of the need to choose an appropriate period for the analysis.…”
Section: Resultsmentioning
confidence: 99%